Plasma electrolytic oxidation of Ti-6Al-4V alloys in nHA/GNS containing electrolytes for biomedical applications: The combined effect of the deposition frequency and GNS weight percentage - Yigit, Oktay; Dikici, Burak; Ozdemir, Niyazi; Arslan, Ersin (Elsevier Science Sa, 2021)
In this study, nano-hydroxyapatite (nHA) based coatings reinforced with graphene nanosheets (GNS) were successfully synthesized on Ti6Al4V alloys using AC-plasma electrolytic oxidation (PEO) technique. The PEO treatments were carried out at 1000, 1500, and 2000 Hz frequencies in different GNS containing electrolytes (free, 1.0, and 1.5 wt%). The combined effect of the deposition frequency and GNS weight percentage on the morphological and crystallographic properties of the coatings was investigated by SEM, AFM, XRD, EDS, and FTIR analysis. The in-vitro corrosion susceptibilities of the coatings were compared by using the potentiodynamic scanning (PDS) technique in simulated body fluid (SBF) at body temperature. Besides, surface hydrophilicity and microhardness measurements were made on the coatings. The characterization of the coatings confirmed that GNS was successfully deposited in nHA-matrix with a porous and rough structure. Coating thickness and hardness increased with increasing GNS weight percentage in the coating layers and deposition frequency. A bone-like apatite formation was also observed on the surfaces after electrochemical tests in SBF. The results revealed that bioactive and hard coatings can be obtained by PEO in nHA/GNS baths.
Keywords: Graphene nanosheet; PEO; Ti6Al4V; Hydroxyapatite; In-vitro corrosion